2010
DOI: 10.1097/jom.0b013e3181c88525
|View full text |Cite
|
Sign up to set email alerts
|

Association of Workplace Chronic and Acute Stressors With Employee Weight Status: Data From Worksites in Turmoil

Abstract: Objectives-To examine the independent and joint effects of psychosocial chronic and acute stressors with weight status and to report the intraclass correlation coefficient (ICC) for BMI.Methods-Baseline data on 2782 employees from a group-randomized weight gain prevention intervention were examined to investigate the effect of high job strain and job insecurity on body mass index (BMI) and on the odds of overweight/obesity including potential confounders and mediating variables. Data were analyzed using mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…23 Height was assessed as a continuous variable, and weight categories provided ranges to decrease nonresponse for what many consider a sensitive variable: 1 = less than 100 lb; 2 = 100 to 129 lb; 3 = 130 to 159 lb; 4 = 160 to 189 lb; 5 = 190 to 200 lb; and 6 = greater than 200 lb. Three sets of BMI estimates were calculated using the minimum, median, and maximum values of the body weight ranges for each category.…”
Section: Study Variablesmentioning
confidence: 99%
“…23 Height was assessed as a continuous variable, and weight categories provided ranges to decrease nonresponse for what many consider a sensitive variable: 1 = less than 100 lb; 2 = 100 to 129 lb; 3 = 130 to 159 lb; 4 = 160 to 189 lb; 5 = 190 to 200 lb; and 6 = greater than 200 lb. Three sets of BMI estimates were calculated using the minimum, median, and maximum values of the body weight ranges for each category.…”
Section: Study Variablesmentioning
confidence: 99%
“…In 18 studies, weight-related outcomes were selfreported (a possible detection bias). A possible attrition bias was found in 3 longitudinal (63, 88, 91) and 3 cross-sectional studies (60,66,89). More than half of the studies (23 out of 36) reported at least one positive association between psychosocial factors at work and a weight-related outcome (table 2).…”
Section: Associations Between Psychosocial Factors At Work and Weightmentioning
confidence: 99%
“…Subsequent physical health issues may also develop, including lack of energy and being accident prone (Coetzee & Klopper, 2010), increased inflammatory process (Goldman-Mellor, Brydon, & Steptoe, 2010), hypertension and coronary artery disease (Hamer et al, 2012;Cora, Partinico, Munafo, & Palomba, 2012), diabetes (Heraclides, Chandola, Witte, & Brunner, 2009, Heraclides, Chandola, Witte, & Brunner, 2012, obesity (Berset, Semmer, Elfering, Jocobshagen, & Meier, 2011;Fernandez, Su, & Winters, & PC, Liang, 2010), and gastrointestinal disorders (Konturek, Brzozowski, and Konturek (2011).…”
Section: Introductionmentioning
confidence: 98%